Chick derived induced pluripotent stem cells by the poly‐cistronic transposon with enhanced transcriptional activity. Issue 2 (24th May 2017) - Katayama, Masafumi; Hirayama, Takashi; Tani, Tetsuya; Nishimori, Katsuhiko; Onuma, Manabu; Fukuda, Tomokazu
Abstract : Induced pluripotent stem (iPS) cell technology lead terminally differentiated cells into the pluripotent stem cells through the expression of defined reprogramming factors. Although, iPS cells have been established in a number of mammalian species, including mouse, human, and monkey, studies on iPS cells in avian species are still very limited. To establish chick iPS cells, six factors were used within the poly‐cistronic reprogramming vector (PB‐R6F), containing M3O ( MyoD derived transactivation domain fused with Oct3/4 ), Sox2, Klf4, c‐Myc, Lin28, and Nanog . The PB‐R6F derived iPS cells were alkaline‐phosphatase and SSEA‐1 positive, which are markers of pluripotency. Elevated levels of endogenous Oct3/4 and Nanog genes were detected in the established iPS cells, suggesting the activation of the FGF signaling pathway is critical for the pluripotent status. Histological analysis of teratoma revealed that the established chick iPS cells have differentiation ability into three‐germ‐layer derived tissues. This is the first report of establishment of avian derived iPS cells with a single poly‐cistronic transposon based expression system. The establishment of avian derived iPS cells could contribute to the genetic conservation and modification of avian species. Abstract : This is the first report of establishment of avian derived iPS cells with a single poly‐cistronic transposon based expression system. Our established iPS cells depend on the activation of FGF signaling pathway, but does not to the LIF signaling.